2022
DOI: 10.1002/aenm.202202333
|View full text |Cite
|
Sign up to set email alerts
|

Direct Characterization of Type‐I Band Alignment in 2D Ruddlesden–Popper Perovskites

Abstract: 2D Ruddlesden–Popper halide perovskites have attracted considerable attention due to their desirable optoelectronic properties, high chemical and structural tunability, and improved environmental stability. However, the understanding of their structure–properties relationships is still limited. In particular, the energy level positions and band alignments at interfaces involving these materials, which are important features to control in the context of any applications, are still under debate. Here, the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The establishment of protocols for efficient synthesis of phase-pure 2D HPs 133,134 could open more opportunities in this regard. 135 For a broad overview of the excitonic properties of the archetypal RP perovskites, readers interested are referred to a comprehensive review by Righetto et al on the subject. 136 One aspect of excitons that is frequently overlooked is the influence of the polar lattice on the exciton itself.…”
Section: Photoexcited Species and Exciton Binding Energymentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of protocols for efficient synthesis of phase-pure 2D HPs 133,134 could open more opportunities in this regard. 135 For a broad overview of the excitonic properties of the archetypal RP perovskites, readers interested are referred to a comprehensive review by Righetto et al on the subject. 136 One aspect of excitons that is frequently overlooked is the influence of the polar lattice on the exciton itself.…”
Section: Photoexcited Species and Exciton Binding Energymentioning
confidence: 99%
“…Compared to phase-pure RP perovskite with n = 1, excitonic properties of 2D HPs with n > 1 layers are challenging to characterize directly by PL and absorption techniques due to the lack of phase-purity. The establishment of protocols for efficient synthesis of phase-pure 2D HPs , could open more opportunities in this regard . For a broad overview of the excitonic properties of the archetypal RP perovskites, readers interested are referred to a comprehensive review by Righetto et al on the subject …”
Section: Fundamental Properties Of Halide Perovskitesmentioning
confidence: 99%
“…Homologous n series of RP perovskites have been shown to have type-I band alignment, which induces carrier funneling and photon recycling from low to high n phases in phase-impure RP perovskite mixtures. 37,38 This effect likely explains why the PL spectra imply a pure or majority high n phase, in contradiction to the absorbance spectra. These results attest to the superior accuracy and sensitivity of absorbance in the spectroscopic determination of the compositions of mixed phase RP perovskite samples.…”
mentioning
confidence: 99%
“…47,48 It has been previously reported that the increase from n = 1 to n = ∞ for lead iodide perovskites results in a type-I, nested bandgap alignment. 37,38 A type-I bandgap alignment is practical for LED applications because carriers can funnel from RP perovskites with the largest energy (smallest n) to lower energy (highest n). 4 Here, we confirm the same type-I alignment trend with the bromide-based RP perovskites (Figure 4c), which provides further support for our previous spectroscopic arguments.…”
mentioning
confidence: 99%
See 1 more Smart Citation